Effects of Adolescent Physical Abuse, Exposure to Neighborhood Violence, and Witnessing Parental Violence on Adult Socioeconomic Status. (May 2013) - Covey, Herbert C.; Menard, Scott; Franzese, Robert J.
Research on the effects of adolescent physical abuse, witnessing domestic violence, and perceptions of community violence have generally, with few exceptions, found them to be predictive of subsequent negative behavioral outcomes, such as substance abuse, crime, and other problem behaviors. Less frequently studied is the relationship of these adverse adolescent experiences to adult socioeconomic statuses. This study utilizes longitudinal self-report data from the National Youth Survey Family Study to investigate how these three factors influence future socioeconomic statuses: marital status, educational attainment, employment, income, and wealth (net worth). Significant associations with adult socioeconomic statuses are found most often for physical abuse, but neighborhood violence is the only one of the three that is predictive of adult employment. Witnessing parental violence is associated with adult income and net worth. Limitations and policy implications of the present research, in the context of past research in this area, are considered.